2021
DOI: 10.3390/molecules26061684
|View full text |Cite
|
Sign up to set email alerts
|

Raman Enhancement of Nanoparticle Dimers Self-Assembled Using DNA Origami Nanotriangles

Abstract: Surface-enhanced Raman scattering is a powerful approach to detect molecules at very low concentrations, even up to the single-molecule level. One important aspect of the materials used in such a technique is how much the signal is intensified, quantified by the enhancement factor (EF). Herein we obtained the EFs for gold nanoparticle dimers of 60 and 80 nm diameter, respectively, self-assembled using DNA origami nanotriangles. Cy5 and TAMRA were used as surface-enhanced Raman scattering (SERS) probes, which e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Also, we observed that 633 nm is the optimal laser wavelength for Raman excitation of Au dimers. 59 We also showed graphene as a protection layer covering the AuNP dimers assembled over nanotriangles. The SERS signals of the TAMRA dyes were still observed after 800 s of continuous irradiation, showing that graphene reduced the photobleaching effect, possibly due to protection from the atmospheric oxygen and by enabling efficient heat dissipation.…”
Section: Single-molecule Platformsmentioning
confidence: 77%
See 1 more Smart Citation
“…Also, we observed that 633 nm is the optimal laser wavelength for Raman excitation of Au dimers. 59 We also showed graphene as a protection layer covering the AuNP dimers assembled over nanotriangles. The SERS signals of the TAMRA dyes were still observed after 800 s of continuous irradiation, showing that graphene reduced the photobleaching effect, possibly due to protection from the atmospheric oxygen and by enabling efficient heat dissipation.…”
Section: Single-molecule Platformsmentioning
confidence: 77%
“…Using fully dye-covered nanoparticles arranged on DNA origami nanotriangles, we studied how the enhancement factor is distributed depending on the size of AuNPs, the chosen dye, and the excitation wavelength. 59 The results showed that AuNPs with a diameter of 60 nm is optimal for obtaining SERS spectra of single dimers. Increasing the diameter to 80 nm only increased the signal slightly, but at the same time, 80 nm AuNPs are significantly more challenging to modify and stabilize.…”
Section: Single-molecule Platformsmentioning
confidence: 97%
“…Roughly 100 DONAs were measured for each nanoparticle dimer design, dye molecule, and excitation wavelength. At the SM level, peak fluctuations have been reported, and at the same time, spectral variations with excitation wavelengths need to be considered Figure SI4 compares SERS and bulk TAMRA spectra at four different excitation wavelengths.…”
Section: Resultsmentioning
confidence: 99%
“…EF for DONAs was determined using the following equation E F D O N A = true( I normalS normalE normalR normalS N normalS normalE normalR normalS true) × true( N normalB normalu normall normalk I normalB normalu normall normalk true) where I SERS and I Bulk are the intensities of most pronounced TAMRA bands (at 1651 cm –1 ), and N SERS and N Bulk are the number of molecules that contributed to the signals. N SERS for fully dye-coated DONA was determined by the number of molecules on the surface of NPs in the hot spot, and N SERS for single-molecule DONA was the molecule conjugated to the Nanofork. N Bulk was determined by the number of molecules in the confocal volume of the laser penetration.…”
Section: Methodsmentioning
confidence: 99%
“…18 Remarkably, since the structure of the double helix is known, DNA origami constructs can be addressed with nm-sized accuracy, thus enabling the placement of desired molecules in a predefined spatial arrangement. DNA origami architectures have been combined with plasmonically active nanostructures leading to hybrid nanomaterials for applications in sensing, 19,20,21 spectroscopy, [22][23][24][25] and biomedical detection methods, 26,27 including single-molecule approaches. 13,28,29 In particular, dimerisation of AuNP has been successfully achieved using origami slit 4 or sheet-like designs.…”
mentioning
confidence: 99%